Pandemia da covid-19 e as implicações na saúde e nas condições de trabalho dos profissionais da enfermagem no Brasil: revisão integrativa. - Santos, Francisco Diógenes dos (2023)
The Covid-19 pandemic has exposed the vulnerability and social problems that have permeated Nursing for decades, in Brazil and around the world; namely: unfavorable conditions, especially due to insufficient material and personnel resources, work overload, low pay, unhealthy working conditions, insufficiency and inadequacy of Personal Protective Equipment, among others. All of these elements have direct consequences for the health and work of these professionals, and favor occupational risks, illness or death. Therefore, the objective of this study is to analyze, in light of the literature, the implications of the Covid-19 pandemic on the health and work of Nursing professionals in Brazil. To this end, the integrative review method is proposed, based on the research question: What are the implications of the Covid-19 pandemic for the health and work of Nursing professionals? formulated through the PICo strategy. The search was carried out in the following databases: International Literature in Health Sciences (MEDLINE), Latin American and Caribbean Literature (LILACS), Bibliographic Database Specialized in the Area of Nursing in Brazil (BDENF); contained in the Virtual Health Library (VHL), between the months of June and July 2023. The following Health Sciences Descriptors were used, in Portuguese: “Nursing”, “Working Conditions” and “Covid- 19”. Such descriptors were combined using the Boolean operators “AND” and/or “OR”. The following inclusion criteria were adopted: works available in full and online; in Portuguese and English and that meet the proposed objective. Duplicate works, course completion works – dissertations, monographs, theses were excluded; editorials, experience reports, summaries of seminars and conferences; documents, opinion articles and those not found in full. The selected studies were synthesized in an Excel® spreadsheet, based on the following information: title, author/authors, year of publication, objective and main results. The level of evidence proposed by Melnyk and Fineout-Overholt (2010) was also used to evaluate the selected studies. 34 articles were analyzed, giving rise to seven empirical categories: Nursing performance in the Covid-19 pandemic: frontline professionals, heroes, angels; Precarious working conditions in Nursing: an old problem worsened by the Covid-19 pandemic; Impact of the pandemic on the health of nursing professionals; Mental health of nursing professionals when facing the Covid- 19 pandemic; Working conditions of Nursing professionals during Covid-19: the global impact of the Pandemic; The role of the media in the construction of Nursing identity; Recognition of the profession: challenges, lessons and future perspectives in nursing. The results found in the literature highlight the challenges faced by Brazilian Nursing, such as low salary appreciation, work overload and lack of human resources. Precarious working conditions have worsened with the pandemic, resulting in stress, anxiety and depression among these professionals. The research emphasizes the need for improvements in working conditions, including adequate provision of Personal Protective Equipment and emotional support, in addition to a National Policy to value these professionals.